PEMINDAIAN DAN PENGOLAHAN LABEL KEAMANAN PADA DOKUMEN RAHASIA DENGAN TITIK KUANTUM - Ratu Bilqis; Jatmiko Endro Suseno; Isnaeni Isnaeni (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Security label is made to anticipate the increasing of documents falsification trend. In this study, the security label is created using CdSe quantum dots. The quantum dots can be used for casting light according to its wavelength so that the particle size can be specific. That’s why its worth to be security key from quantum dots. The quantum dots that be used is colloidal CdSe quantum dots with a wavelength of 595 nm and 526 nm. In the previous studies have been done the two-dimensional scanning process of quantum dots for one color as a security label. However, the results obtained are not perfect because it has not done the repair process for the image resulted. Therefore, in this study conducted by the two-dimensional scanning of quantum dots in two colors to add a level of security on the label then followed by image processing in order to obtain a better image. Image processing which have been done by observing the histogram of the image in order to obtain a threshold value between the object and the background image. Scanning generate data in the form of a sequence intensity value corresponding to the color intensity of quantum dots to obtain image data processing results. Image processing through the observation of the histogram data successfully get the intensity threshold value so that the image can be processed to become more visible in accordance with the sample